Ekonomi Islam Dalam Perspektif Maqasid Asy-Syariah - Fira Mubayyinah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2019)
Abstract Islamic economics regulates various economic activities based on Islamic Shari'a by avoiding Maisyir, Gharar, Haram, Dzalim, Efforts and Usury. The characteristics of Islamic economics uphold the protection of individual ownership aimed at the good and interests of happiness in the world and the hereafter. At least now Indonesia has more than 12 Islamic banks, 22 Islamic business units and more than 80 units of sharia-based public finance institutions that are spread throughout the region. The presence of economic institutions based on Islamic teachings is an indicator that society needs to get equitable welfare because the Islamic economy adheres to the principle of balance. This research is classified as normative research, using conceptual approaches, then critically analyzed. The results of the study show that the application of the Islamic economy is in line with the goal of Islamic law (Maqasyid Asy-Shari'ah), which is the benefit of the people in the world and the hereafter. Maqasid Asy-Syariah as a foundation for thinking to develop progressive and dynamic Islamic economics. Keywords: Islamic Economy, Maqasid As-Shari'ah